English Language Training for Tourism Development Using Travel Guide Book (TGB) in Negeri Oma, Central Maluku - Juvrianto Chrissunday Jakob; Ahmad Nusi; Meyke Marantika; Sylvia Irene Persulessy (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The role of language in tourism is very significant, knowing tourism knowledge, especially about objects and attractions, is an important insight for people who live in tourist areas. Based on initial observations, the community service team observed that human resources in Negeri Oma have not yet developed their ability to promote tourism, particularly in communication. As a simple example, when there are foreign tourists who ask for directions or ask for directions to where to stay, local residents still have difficulty in explaining it. Related to the problems that community service team got from initial observations in the field, the team carried out English language training to develop foreign language mastery for residents in Negeri Oma, Haruku Island, Central Maluku. The service team provides training to junior and senior high school students to practice their English skills. The results of this training showed the high interest and motivation of the students who were given the training. Furthermore, after going through several training sessions, students were able to practice simple conversations such as introducing themselves, showing directions to tourist attractions, and haggling over the price of souvenirs. This training is also expected to produce a product, namely a guide that can be used by the community that contains simple conversations in English in terms of tourism.